Study on Endophytic Fungi Associated with Moringa oleifera Lam. Collected from Lombok Island, West Nusa Tenggara - Ramadhani, Indriati; Rohadi, Hasnadiazahra; Yuliani, Yeni; Ilyas, Muhammad (Annales Bogorienses, 2020)
An assemblage of endophytic fungi was isolated from Moringa oleifera Lam. collected from Lombok island, West Nusa Tenggara Province, Indonesia. Fungal endophytes were isolated using surface sterilization methods with slight modification. Forty-six selected endophytic fungal strains were isolated from the leaves, petioles, and stems of M. oleifera. The fungal strains identification through morphological observation and ITS rDNA-based molecular analysis showed that fungal endophytes were associated with host plants belonging to the taxa Alternaria, Cladosporium, Colletotrichum (Glomerella), Corynespora, Curvularia (Cochliobolus), Fusarium, Mucor, Ochrocladosporium, Phomopsis (Diaporthe), and Trametes. In this study, endophytic Phomopsis dominating the obtained strains, whereas 26% (12/46) strains were isolated from host plant samples.